The Roles of IL-1 Family Cytokines in the Pathogenesis of Systemic Sclerosis - Xu, Dan; Mu, Rong; Wei, Xiaofan (Frontiers in Immunology, 2019)
The IL-1 family consists of 11 cytokines, 7 ligands with agonist activity (IL-1𝛼, IL-1𝛽, IL-18, IL-33, IL-36𝛼, IL-36𝛽, IL-36𝛾) and 4 members with antagonistic activities (IL-1 receptor antagonist (IL-1Ra), IL-36Ra, IL-37, IL-38). Recent articles have described that most members of IL-1 family cytokines are involved in the process of innate and adaptive immunity as well as fibrosis in systemic sclerosis (SSc). IL-1 family gene polymorphisms, abnormal expression of IL-1 and its potential role in the fibrosis process have been explored in SSc. IL-33 and IL-18 have also been discussed in the recent years. IL-33 may contribute to the fibrosis of SSc, while IL-18 remains to be researched to confirm its role in fibrosis process. There is a lack of study on the pathophysiological roles of IL-36, IL-37 and IL-38 in SSc, which might provide us new study area. Here, we aim to give a brief overview of IL-1 family cytokines and discuss their pivotal roles in the pathogenesis of SSc.